Ethico-spiritual dimensions of charity: an Islamic perspective - Bensaid, Benaouda (IDOSI Publications, 2013)
Benevolence known in Islam as sadaqa is an integral component of Muslim religiosity. Muslims are generally accustomed to giving away charity as sign of religious devotion and care of the poor and needy in society. Yet while the significance of giving is a common practice in Muslim societies, the understanding of its ethico-spiritual dimensions is not; and requires further research. This paper sheds light on the multifaceted nature of sadaqa and how it is perceived not only as a means of spiritual purification, but also as factor of building socio-economic sustainability. This research draws on Islamic literature pertaining to the concepts, norms and laws of sadaqa in Islam to provide a conceptual framework of analysis of charity and its respective practice in Islam and thus supplies researchers with the perspective necessary for further interpretation and analysis on Islamic philanthropy.